2014
DOI: 10.1001/jamasurg.2014.675
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Colorectal Enhanced Recovery After Surgery in a Community Hospital

Abstract: Implementation of this patient care-directed enhanced recovery program is feasible in a community hospital setting, and it is associated with decreased LOS without increased readmission or morbidity, as well as significant decreases in narcotic use and cost. Improved outcomes are independent of the laparoscopic approach and CRC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 28 publications
4
80
0
Order By: Relevance
“…No significant differences were found for readmission rates, surgical complications and mortality. This review found several other studies with consistent conclusions in colorectal surgery, reporting that ERAS programs reduce LOSH [36][37][38][39][40][41][42]. Shida et al [43] found these same results in patients operated for obstructed colorectal cancer.…”
Section: Colorectal Surgerysupporting
confidence: 55%
“…No significant differences were found for readmission rates, surgical complications and mortality. This review found several other studies with consistent conclusions in colorectal surgery, reporting that ERAS programs reduce LOSH [36][37][38][39][40][41][42]. Shida et al [43] found these same results in patients operated for obstructed colorectal cancer.…”
Section: Colorectal Surgerysupporting
confidence: 55%
“…Other studies 27,29 have highlighted how surgeons can be slow to embrace ERAS owing to concerns about increased readmission risk, lack of resources required to implement the ERAS protocol, and the worry that the burden of recovery may not be transferable to outpatient and community services by discharging patients sooner. However, as demonstrated here, the implementation of an ERAS protocol is safe, efficacious and cost-effective 2,3,25,29 . As the field of structured perioperative care continues to evolve, surgeons and other healthcare providers must be able to adapt and incorporate these changes into their clinical practices.…”
Section: Discussionmentioning
confidence: 65%
“…Promoting the adoption of evidence-based best practices, ERAS programmes focus on patient education, goal-directed fluid management, decreased use of unnecessary nasogastric tubes and peritoneal drains, minimal use of opioid analgesia, as well as early mobilization and resumption of oral intake 1,3,5,6 . Widely adopted for colorectal and orthopaedic surgery, these programmes have been effective in reducing length of stay and morbidity while improving the value of care and patient satisfaction after surgery 1,2,7 . Liver resection is the primary treatment for many different types of hepatopancreaticobiliary disease 8 -10 .…”
Section: Introductionmentioning
confidence: 99%
“…The ERP is a comprehensive perioperative CRS care pathway that has been shown to reduce postoperative morbidity and length of hospitalization. [9][10][11][12][13][14][15][16][17] Similarly, the SSIB is a perioperative care program that systematically provides evidence-supported measures for surgical wound infection prevention and has been shown to reduce the rate of postoperative wound infection. [18][19][20][21][22] Although both the ERP and SSIB have individually been shown to improve outcomes after CRS, the effect of their combined presence has not, to our knowledge, previously been reported in the literature.…”
mentioning
confidence: 99%